Upaya Peningkatan Motivasi Hafal Al-Qur’an Bagi Lansia di MTRJ, Lhokseumawe, Aceh - Latif, Hamdiah (Prodi Pengembangan Masyarakat Islam STAIN Teungku Dirundeng Meulaboh, 2022)
This article would like to discuss about overview of self-determination on elderly people who memorize Al-Qur’an. As we know, elderly people usually have various degradations on their physical, cognitive, and psychosocial function. By using a qualitative descriptive approach as the method, this study would like to know how elderly people who are more than 60 years old, are motivated to memorize Al-Qur’an through the program “Sehari Bersama Al-Qur’an” which held in Majelis Taklim Raudhatul Jannah (MTRJ) Lhokseumawe. The result of the study shows that participants had some shifting of motivation that once external changed into internal motivation and a different description of self-determination between the participants which helps them to memorize Al-Qur’an and face their obstacle during the process. The result indicated that there is a significant affect of motivation and self-determination on elderly people who memorize Al-Qur’an in MTRJ, Lhokseumawe.